The effects of country of origin (COO) on halal consumption: Evidence from China - Meenchee, Hong; Kamaruddin, Roslina (Universiti Putra Malaysia Press, 2020)
In China, the demand for halal products is sizable. However, halal product adulteration is common, and product authenticity is doubtful due to the unknown origin of the products. To date, literature addressing China’s Muslims’ demand for halal products and the role of country of origin (COO) on China’s Muslims’ halal personal care product consumption have been limited. The purpose of this study was to explore if the COO influences China’s Muslims purchase decision on halal personal care products in China. The research used the Revealed Preference Theory to determine the effects of COO on China’s Muslims’ purchasing decisions for halal products. Using the cross-sectional survey method, data was collected from Muslims living in northwest China and processed-analysed using a logit model application. The results of the study revealed that the COO of halal products is an important concern for China’s Muslims, with other selection criteria that also influence the purchase decision. It is clear that COO is an important indication of the authenticity of halal products for China’s Muslims. As well, this paper provides the notion that COO is one of the important selection criteria for (consumers’ trust in the products) of halal consumption in a non-Muslim country.